2016
DOI: 10.1111/ajco.12567
|View full text |Cite
|
Sign up to set email alerts
|

Number of negative lymph nodes as a prognostic factor in esophageal squamous cell carcinoma

Abstract: The number of NLNs, which represents the extent of lymphadenectomy for esophageal squamous cell carcinoma, could impact the overall survival of patients with resected esophageal squamous cell carcinoma, especially among those with nodal-positive disease and advanced T-stage tumor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 18 publications
1
17
0
Order By: Relevance
“…However, recent reports have shown that the number of NLN also plays an important role in the prognosis of patients with ESCC that have undergone radical resection of ESCC (18,19). The current study also con rmed that the number of NLN removed in lymphadenectomy was closely associated with the outcome of patients, and further investigation revealed the number of NLN inside the thoracic cavity was an independent predictor for prognosis while the number of NLN outside the thoracic cavity was not an independent prognostic factor.…”
Section: Discussionsupporting
confidence: 74%
“…However, recent reports have shown that the number of NLN also plays an important role in the prognosis of patients with ESCC that have undergone radical resection of ESCC (18,19). The current study also con rmed that the number of NLN removed in lymphadenectomy was closely associated with the outcome of patients, and further investigation revealed the number of NLN inside the thoracic cavity was an independent predictor for prognosis while the number of NLN outside the thoracic cavity was not an independent prognostic factor.…”
Section: Discussionsupporting
confidence: 74%
“…Baba et al [11] investigated 252 patients with In this retrospective analysis, we evaluated the impact of NLNs number on the survival of a total of 579 thoracic ESCC patients from a single center who all received cura-tive esophagectomy. Ma et al [13] demonstrated that ESCC patients with more than 20 NLNs have better survival rates in contrast to those with less than or equal to 20 NLNs, through retrospective analysis of 381 patients who had underwent surgical resection. Zhang et al [19] retrospectively analyzed 99 patients who were identified with middle thoracic ESCC after esophagectomy and found obvious differences of OS between the following groups: patients with more than and less than 10 NLNs and patients with>15 and ≤15 NLNs.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years,the number of NLNs has been confirmed to be an important factor related to patient survival in many cancers, proving to be more accurate than the number of positive LNs in predicting patients' prognosis [8][9][10]. Several papers have scrutinized the impact of NLNs on patient survival for EC [11][12][13]. Greenstein et al [12] found that an increasing NLNs count was related to with long-term patient survival in those with lymph node-negative esophageal adenocarcinoma but not in those with the squamous cell subtype.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study also showed that the number of negative lymph nodes (NLNs) could impact the OS of patients with ESCC, especially among those with nodal-positive disease and advanced T-stage tumor [ 16 ]. The prognostic value of NLNs was also confirmed in previous studies that revealed that a higher number of NLNs was associated with better OS in EC patients after esophagectomy [ 17 18 ].…”
Section: Introductionmentioning
confidence: 99%